Dissensus in Ali Smith’s Seasonal Quartet - Heynders, Odile (FRAME, Journal of Literary Studies, 2026)
In the context of debates on how democracies function in a digital, mediatized and global context, this contribution asks if (and how) the literary novel can be effective in today’s public spheres. What role is there for fiction in the neoliberal world in which we are absorbed by commercial social media, attention spilling technological devices, and the dissemination of truth? Drawing on Rancière’s ideas on the politics of literature and art’s capacity of dissensus, the seasonal quartet (2016-2020) by British author Ali Smith will be analyzed and discussed. The main argument of this hermeneutic project is that Smith creates an opening in fiction to artistic perception, historical materiality, social voices and dissensus, while representing timely controversies in British society.